Editorial - article Editorial (Сеченовский вестник)
Dear colleagues, In the end of 2019, the world faced a new threat — COVID-19 caused by the new coronavirus SARS-CoV-2. On March 11, 2020, the World Health Organization declared the beginning of the pandemic. In Russia, the maximum number of cases was registered in Moscow: as of the end of September 2020, their number exceeded 300 thousand. Since the 19th of March 2020, a Federal Remote Advisory Center for Anesthesiology and Resuscitation for Adults has been functioning at Sechenov University, a leading medical HEI in Russia. Highly qualified specialists consult 24/7 the most severe COVID-19 patients from all regions of the Russian Federation. 2,919 staff members of Sechenov University participated in treatment of 6,009 COVID-19 patients on the bases of four University hospitals during the period from April 8 till August 10, 2020. Considering the vast experience in the diagnosis and treatment of COVID-19 accumulated by the University and our colleagues during the pandemic, a decision has been made to devote one of the Sechenov Medical Journal issues to this problem. The issue covers a wide range of COVID-19 associated problems: the pathogenesis of the disease, diagnostic capabilities of ultrasound examination of lungs, treatment features for oncology patients, cardiovascular safety assessment of hydroxychloroquine combined with azithromycin, effectiveness of corticosteroids, features of damage to the organ of vision, legislative regulation of health protection in an epidemic. We very much hope, the information in this issue will help fighting against this dangerous infection!